African Linguistics Across The Disciplines: Selected Papers From The 48th Annual Conference On African Linguistics - Lotven, Samson; Bongiovanni, Silvina; Weirich, Phillip; Botne, Robert; Obeng, Samuel Gyasi (My University, 2019)
Since the hiring of its first Africanist linguist Carleton Hodge in 1964, Indiana University’s Department of Linguistics has had a strong and continuing presence in the study of African languages and linguistics through the work of its faculty and of its graduates on the faculties of many other universities. In 1972, the Indiana University Department of Linguistics hosted the third Annual Conference of African Linguistics. Proceedings of that conference were published by Indiana University Publications (African Series, vol. 7). In 1986, IU hosted the seventeenth Annual Conference of African Linguistics with Paul Newman and Robert Botne editing the proceedings in a volume entitled Current approaches to African linguistics, vol. 5. In 2016, Indiana University hosted the 48th Annual Conference on African Linguistics with the theme African linguistics across the disciplines. Proceedings of that meeting are published in this volume. The papers presented in this volume reflect the diversity of opportunities for language study in Africa. This collection of descriptive and theoretical work is the fruit of data gathering both in-country and abroad by researchers of languages spoken across the continent, from Sereer-Siin in the west to Somali in the northeast to Ikalanga in the south. The range of topics in this volume is also broad, representative of the varied field work in country and abroad that inspires research in African linguistics. This collection of papers spans the disciplines of phonology (both segmental and suprasegmental), morphology (both morphophonological and morphosyntactic), syntax, semantics, and language policy. The data and analyses presented in this volume offer a cross-disciplinary view of linguistic topics from the many under-resourced languages of Africa.
Keywords: African linguistics; Annual Conference; linguistics